Teachers’ Perceptions, Attitudes, And Subjective Norms On Teenage Pregnancy Prevention In Jambi High Schools - Yessa Praditha Putri; Adelina Fitri; Muhammad Syukri; Rd. Halim (CV. AFDIFAL MAJU BERKAH, 2026)
Teenage pregnancy is a health and social issue that impacts adolescents’ education and future. The involvement of schools and teachers in prevention efforts is influenced by their perceptions, attitudes, and subjective norms regarding teenage pregnancy. This study aims to explore in depth the perceptions, attitudes, and subjective norms of high school teachers regarding efforts to prevent teenage pregnancy in Jambi City. This study employs a qualitative approach with a phenomenological study design. The informants consisted of 18 individuals, including school principals, vice principals for student affairs, biology teachers, religion teachers, guidance counselors, and homeroom teachers from three public high schools in Jambi City. Data were collected through in-depth interviews, observations, and documentation, then analyzed inductively through coding, categorization, and theme identification. The results of the study indicate that teachers view teenage pregnancy as a serious issue and support prevention through guidance, education, counseling, student monitoring, and collaboration with parents and external parties. Strengthening school-based reproductive health education, teacher capacity, parental involvement, and cross-sectoral collaboration are necessary to optimize prevention.